Simple technique to manage redundant skin after laparoscopic ventral hernia repair. Issue 2 (22nd April 2013) - Karim, Muhammad Ali; Ali, Abdulmajid
Abstract Introduction The redundant skin left behind after laparoscopic ventral hernia repair overlies a dead space that is a potential site for seroma formation. This predisposes patients to surgical‐site infection and compromises the cosmetic outcome of the procedure, which is a key feature of the minimally invasive approach. We present a simple technique to deal with this problem. Materials and Surgical Technique This technique was used in six patients who underwent laparoscopic ventral hernia repair. Two patients were men and four were women. At the end of the procedure, glue (fibrin sealant) was injected in the dead space underneath the redundant skin and pressure was applied for some time; this attached the excessive skin to the underlying tissue. This obliterated the potential dead space, reducing the chances of seroma formation, and improved the cosmetic outcome of the procedure. Patients were reviewed 8 weeks after the procedure, and their body contours had returned to normal, with no skin redundancy. Discussion Minimally invasive surgery offers the advantage of a shorter hospital stay, faster recovery and improved cosmetic outcome, achieving better patient satisfaction as a result. This simple technique at the end of laparoscopic ventral hernia repair, in which the redundant skin is attached to the underlying tissue, improves the immediate postoperative cosmetic outcome and also obliterates any potential dead space for seroma formation.